Training and Feasibility Study of Oyster Mushroom Cultivation at Ganda Mandiri Farmer Group in Sukamanah Village, Ciamis Regency - Khusnul Khusnul (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Oyster mushroom cultivation is one solution for improving a community’s economy. In mushroom cultivation, is necessary to pay attention to various things that support the success of its production. The success of the production of seeds and bag logs of oyster mushrooms is an indicator of feasibility in this business. Success in production can be judged from a large amount of production enabled by hyalinizing the risk of failure. The parameters of the feasibility or success of the business require a cost analysis that is appropriate to the conditions and needs. One of the farmer groups that carry out mushroom cultivation business is Ganda Mandiri Farmer Group in Sukamanah Village, Ciamis Regency. The purpose of this community service was to increase the target farmers’ understanding and improve their skills in mushroom cultivation and determine the feasibility of oyster mushroom cultivation for the farmer group. The methods used during this activity were interviews and direct observation of the farmer group’s business activities. After the counseling and training, it was found that the farmer group’s members showed a significant increase in their skills, especially in making seeds. This farmer group could produce as many as 7,200 bag logs within 4 weeks. The result of the analysis of the R/C ratio was 2.51. The results of the cost analysis could be used as an indicator of the feasibility for a business, and the oyster mushroom cultivation business run by Ganda Mandiri Farmer Group was said to be feasible and profitable.